2013
DOI: 10.1007/s00381-013-2323-1
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen years of experience with the midfacial distraction without maxillary osteotomy protocol

Abstract: Compared to other techniques, this method is safe, simple and efficient. By sparing major osteotomies, it avoids severe complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The technique is easy and fast, and employs very basic, external hardware with low complication rates. 71 Using transfacial pins for midface distraction in very young patients with midface retrusion and distortion is challenging with a high morbidity rate due to iatrogenic orbital and tooth bud injury 27,70,72 and technical failure, due to their deformed skull and hypoplastic midface. Lack of maxillary growth and an abnormal remodeling pattern results in small-sized bone structure and disorganized architecture in syndromic craniosynostosis (e.g., small zygoma and maxilla, and a high, arched palate).…”
Section: Rationale For the Choice Of Technique And Utility Of Roboticsmentioning
confidence: 99%
See 2 more Smart Citations
“…The technique is easy and fast, and employs very basic, external hardware with low complication rates. 71 Using transfacial pins for midface distraction in very young patients with midface retrusion and distortion is challenging with a high morbidity rate due to iatrogenic orbital and tooth bud injury 27,70,72 and technical failure, due to their deformed skull and hypoplastic midface. Lack of maxillary growth and an abnormal remodeling pattern results in small-sized bone structure and disorganized architecture in syndromic craniosynostosis (e.g., small zygoma and maxilla, and a high, arched palate).…”
Section: Rationale For the Choice Of Technique And Utility Of Roboticsmentioning
confidence: 99%
“…73 The age profile of our patients with midface distraction is much younger than that reported in other series. 22,[36][37][38][39]70 Compared with traditional osteotomy techniques, the technique of using transfacial pins 27,70 allowed us to ad-dress midface distraction considerably early, when the maxillary-zygomatic junction is relatively fragile, and with reduced blood loss. 70 Although previous authors have used either a freehand technique 70 or navigation to perform the same, 71 robotic assistance allowed the safe passage of the pin in a predetermined trajectory with respect to the globe and tooth buds (Fig.…”
Section: Rationale For the Choice Of Technique And Utility Of Roboticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The timeframe of development of sinusitis and mucoceles is highly variable. For example, Coeugniet et al 17 reported the development of maxillary sinusitis in one patient with Crouzon syndrome and one with Apert syndrome within seven days of craniofacial surgery. Tatla et al 19 , reported on a 12-year-old boy with Crouzon syndrome that developed frontoethmoidal mucoceles 18-months post-surgery.…”
Section: Sinusitis As a Post-operative Complicationmentioning
confidence: 99%
“…Furthermore, the use of an external device avoids the risk of infection related to intra-focal devices. [52][53][54][55]56].…”
Section: International Archives Of Medicinementioning
confidence: 99%